Evaluation of the freshness of rainbow trout (Oncorhynchus mykiss) fillets by the NIR, E-nose and SPME-GC-MS. Issue 19 (13th April 2022) - Xu, Kunli; Yi, Yuwen; Deng, Jing; Wang, Yuanhui; Zhao, Bo; Sun, Qianran; Gong, Chenhui; Yang, Zepeng; Wan, Hailun; He, Ruiyan; Wu, Xinyu; Yao, Bo; et al.
Abstract : Successful evaluation of rainbow trout ( Oncorhynchus mykiss ) fillet freshness using the NIR and E-nose non-destructive techniques combined with SPME-GC-MS. Abstract : A comparison study on the freshness of rainbow trout ( Oncorhynchus mykiss ) fillets in the course of their sale was performed using near-infrared spectroscopy (NIRS), solid-phase microextraction combined with gas chromatography-mass spectrometry (SPME-GC-MS), and the electronic nose (E-nose) technique. Quantitative analysis of the volatile salt nitrogen (TVB-N) of rainbow trout fillets with different freshness using NIR combined with the partial least squares (PLS) method revealed that the predicted values of TVB-N of the samples were significantly correlated with the true values ( P < 0.01). SPME-GC-MS combined with E-nose analysis demonstrated that there were significant differences in the volatile flavor components of rainbow trout fillets at different freshness, and E-nose combined with principal component analysis (PCA) and linear discriminant analysis (LDA) could achieve rapid and non-destructive freshness ranking of rainbow trout fillets based on volatile flavor characteristics. Consequently, the NIRS and E-nose non-destructive testing techniques are capable of acting as rapid screening tools for detecting the freshness of rainbow trout fillets during their sale.